Implicaciones de la neurociencia en el desarrollo cognitivo en niños/as de educación inicial de la escuela Once de Noviembre de la provincia de Cotopaxi cantón Latacunga en el año lectivo 2016 – 2017 - Tipan Guashca, Geovanna Jessica (2017)
The research purpose was to look into in the scientific basis from the neuroscience perspective; it can help to improve the cognitive development in children of preschool education. For this reason, it was conducted a literature review of documentary sources on the neuroscience main findings to Education, subsequently it was conducted a field study at “Once de Noviembre” and “Isidro Ayora” School. The research design was qualitative-quantitative approach which allows developing a description of the neuroscience impact in education. The instruments used were the survey and the checklist. Firstly, it applied the questionnaire to the teachers in order to measure their knowledge and the implementation level of strategies in the classroom based on neuroscience. In the second place, it was carried out the direct observation in the institutions to analyze the strategies used by the teachers with the aim to optimize the children cognitive development. Finally, a proposal was made to implement educational activities based on the neuroscience in the school environment in order to try to improve the lack which exist in the teachers activities include on time to teach the classes….